AVALIAÇÃO DA ATIVIDADE ANTIFÚNGICA DE EXTRATOS NATURAIS E PRÓPOLIS SOBRE CANDIDA spp. – ESTUDO IN VITRO - Silva, Rosana Marques (2012)
The denture stomatitis is an inflammation of the oral tissues which keeps direct contact with the prostheses. For the treatment of this disease, the use of natural extracts is promising, however, studies of their antimicrobial activity of different extracts should be expanded. Thus, the aim of this study is to evaluate in vitro antifungal activity of natural extracts of medicinal plants and propolis on strains of Candida spp. For this we used hydroalcoholic extracts of Malva sylvestris (malva) and Azadirachta indica (neem) at concentrations of 1:1, 1:2 and 1:4. The hydroalcoholic extract of propolis at concentrations of 20 and 30 was used.The tests were done in duplicate. The extracts were impregnated in sterile paper disks and “inhibition zone” were measured in mm with a caliper. The plates were incubated at a temperature of 37 ± 0.5 C until the development of the colonies. The antifungal activity was evaluated after 48h in the different treatments. Subsequently, the broth microdilution test for determining the minimum inhibitory concentration (MIC) was also performed. Data were evaluated statistically with significance levels of p <0.05 and descriptive analysis. In disk diffusion testing, the extracts were not effective. The extracts which inhibited over 50 of fungal growth were considered effective. The MIC of propolis to C. albicans, C. glabrata, C. krusei was 30 and to C. tropicalis was 20. The malva showed no inhibition percentage above 50 for any strain evaluated. The MIC for neem was 1:1 for C. glabrata and C. krusei, and 1:2 to C. tropicalis. This plant didn’nt showed inhibition to greater than 50 to C. albicans. The results show that plants and propolis under study had limited effectiveness against the strains studied. Future studies of the action of extracts of these plants should be conducted.